Evaluation of the clinical efficacy of microwave ablation for benign thyroid nodules based on contrast-enhanced ultrasound - Zhang, Yun; Feng, Jun; Fu, Gang (Medicine (Baltimore), 2024)
This study evaluates the clinical efficacy of microwave ablation in patients with benign thyroid nodules based on contrast-enhanced ultrasound. A total of 92 patients with benign thyroid nodules admitted to our hospital from January 2020 to December 2022 were selected as research subjects and divided into control group and observation group according to different treatment methods, with 46 cases in each group. All patients received microwave ablation. Imaging examination and monitoring were performed before and after microwave ablation. The control group underwent routine ultrasound examination, and the observation group underwent contrast-enhanced ultrasound examination. It was determined whether or not to terminate ablation therapy according to the imaging examination results. Results of enhanced MRI were used as the gold standard to evaluate the clinical efficacy, thyroid nodule volume, thyroid nodule volume reduction rate, nodule recurrence, and complication rate of the 2 groups. Using the results of enhanced MRI as the gold standard, the total ablation rate of observation group was 96.55%, which was significantly higher than that of control group 85.96%, and the nodule survival rate of 3.45% was significantly lower than that of control group 14.04% (P < .05). After 1 month, 3 months, 6 months, and 12 months, the thyroid nodule volume of both groups was significantly reduced, and the thyroid nodule volume of observation group was significantly smaller than that of control group (P < .05). After 1 month, 3 months, 6 months, and 12 months, the reduction rate of thyroid nodule volume in 2 groups was significantly increased, and the reduction rate of thyroid nodule volume in observation group was significantly higher than that in control group (P < .05). After treatment, the recurrence rate of nodule in observation group was 4.35%, which was significantly lower than that in control group, 15.22% (P < .05). After treatment, the complication rate of observation group was 8.70%, which was significantly lower than that of control group 26.09% (P < .05). Contrast-enhanced ultrasound can effectively monitor the treatment range of benign thyroid nodules by microwave ablation, improve clinical efficacy, reduce the recurrence rate of nodules, and has high effectiveness and safety.